2011
DOI: 10.1002/anie.201103110
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Biosynthesis: Modularity Rules

Abstract: Terpenes are the largest class of small molecule natural products on Earth, and the most abundant by mass. Here, we summarize recent developments in elucidating the structure and function of the proteins involved in their biosynthesis. There are 6 main building blocks or modules (α,β,γ,δ,ε and ζ) that make up the structures of these enzymes: the αα and αδ head-to-tail trans-prenyl transferases that produce trans-isoprenoid diphosphates from C5 precursors; the ε head-to-head prenyl transferases that convert the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
301
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 333 publications
(317 citation statements)
references
References 92 publications
(130 reference statements)
5
301
1
10
Order By: Relevance
“…This multiple targeting is expected to be of importance in overcoming the development of drug resistance because targeting membrane physical properties is expected to be less susceptible to the development of resistance. molecular dynamics simulations | clofazimine | bedaquiline | clomiphene | vacquinol T here is a need for new antibiotics, due to the increase in drug resistance (1,2). For example, some studies report that by 2050, absent major improvements in drug discovery and use, more individuals will die from drug-resistant bacterial infections than from cancer, resulting in a cumulative effect on global gross domestic product of as much as 100 trillion dollars (3,4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This multiple targeting is expected to be of importance in overcoming the development of drug resistance because targeting membrane physical properties is expected to be less susceptible to the development of resistance. molecular dynamics simulations | clofazimine | bedaquiline | clomiphene | vacquinol T here is a need for new antibiotics, due to the increase in drug resistance (1,2). For example, some studies report that by 2050, absent major improvements in drug discovery and use, more individuals will die from drug-resistant bacterial infections than from cancer, resulting in a cumulative effect on global gross domestic product of as much as 100 trillion dollars (3,4).…”
mentioning
confidence: 99%
“…Therapy is lengthy, even with drug-sensitive strains, and requires combination therapies with four drugs. Two recent TB drugs/drug leads (9)(10)(11) are TMC207 [bedaquiline (1); Sirturo] and SQ109 (2) (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31) It has been reported that many terpene cyclases have broad substrate specificities, and that other classes of terpenes have been created in vitro. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] A combination of studies identifying enzymatic products biosynthesized from unusual substrates and the analysis of genome sequences should lead not only to the discovery of additional functions of these enzymes in the organism, but also to the identification of novel natural terpenoids that have functions in their producers.…”
Section: Identification Of Bifunctional Sesquarterpene/ Triterpene Cymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] These compounds including hormones, vitamins, drugs, flavorings, and pigments, are categorized by number of C 5 isoprene units, as follows: hemi-(C 5 ), 1 unit; mono-(C 10 ), 2 units; sesqui-(C 15 ), 3 units; di-(C 20 ), 4 units; sester-(C 25 ), 5 units; tri-(C 30 ), 6 units; and tetraterpenes (C 40 ), 8 units. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In contrast, little is known about C 35 terpenes. To the best of my knowledge, only 19 cyclic and eight linear C 35 terpenes have been identified to date, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]…”
mentioning
confidence: 99%